(untitled) (E Global Congress, 2025)
Innovation is becoming a key factor in human development and economic growth. The continuous development of the innovation process has a serious impact on the change of humanity and social life. Innovation has a great impact on the modernization of economic entities. Effective innovative activity determines not only the production strategy, but also the strengthening of the country’s economic potential. Innovation includes the creation or improvement of a product (goods, work, service) in a new form, the introduction of a new view of the production process or the improvement of this process, the introduction of new marketing or organizational methods in conducting business, the creation of jobs, or the establishment of external relations. the final result of the activity is understood.